Developing Caring Economics-Based Teaching Materials for Microeconomics: A Design-Based Research Study on Altruism and Social Responsibility in Higher Education - Suyono, Akhmad; Wahyono, Hari; Wardoyo, Cipto; Nasikh; Eka Putri, Miranti (Asian Journal of Interdisciplinary Research, 2026)
The economic rationality and low level of social concern among university students indicates that economic learning in higher education does not adequately integrate altruistic values. Learning materials are predominantly influenced by a neoliberal paradigm, which tends to shape students’ perspectives toward individual rationality as homoiconic. This condition highlights the need for innovative learning approaches that balance economic rationality with social responsibility. Therefore, this study aims to develop a caring economics–based learning model in higher education to internalize altruistic values in students’ economic activities. The study employed a design-based research (DBR) approach involving problem identification, design development, implementation, and revision. The developed Caring Economics–based microeconomic learning design and teaching materials were implemented in classroom practice and evaluated using pretest–posttest and situational judgment test to examine its practicality and effectiveness in fostering students’ altruistic economic attitudes and perspectives. This study develops Caring Economics–based teaching materials for a microeconomic theory course using a design-based research (DBR) approach. The materials demonstrated high feasibility, with validation scores ranging from 86.67 to 100.00 across organizations, case selection, language clarity, visual presentation, and integration of Caring Economics. Classroom implementation improved lecturer activity (66%–88%) and student participation (64%–83.6%). Learning effectiveness was confirmed by an N-Gain score of 0.75 (high category). The Wilcoxon Signed Rank Test showed a significant difference between pretest and posttest scores (Z = -3.923, p < 0.05), leading to the rejection of H₀. These results indicate that the caring economics–based microeconomics textbook significantly improved students’ learning outcomes. Conclusion. These findings suggest that integrating Caring Economics into microeconomic learning enhances students’ conceptual understanding while fostering altruistic values. Therefore, Caring Economics offers a meaningful pedagogical approach for strengthening both students’ economic competence and their social responsibility in economic decision-making.